MEDIA PEMBELAJARAN BERDIFERENSIASI PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR : SYSTEMATIC LITERATURE REVIEW - Kurniawan, Romi; Eka Sriwahyuni; Elsinora Mahananingtyas; Seno Lamsir; Dhiemas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of Indonesia's Kurikulum Merdeka highlights the urgency of differentiated learning to address student heterogeneity in Elementary Schools, particularly in Integrated Science and Social Studies (IPAS). However, there is a lack of systematic mapping regarding differentiated learning media specific to this context. This study aims to identify, evaluate, and synthesize evidence on differentiated learning media in IPAS at the elementary level. Using a Systematic Literature Review (SLR) design following the PRISMA 2020 protocol, data were collected from six databases (Scopus, Web of Science, Google Scholar, ERIC, Garuda, SINTA) published between 2015 and 2025. Fifteen studies met the inclusion criteria and were analyzed using narrative synthesis and thematic analysis. Results indicate that digital media dominates (66.7%), particularly Google Sites and Augmented Reality. These media significantly improve cognitive understanding (20–45% increase), psychomotor skills, and affective domains, with motivation rising up to 93%. Successful implementation relies on teacher competence (TPACK) and infrastructure availability, though challenges persist in remote areas. This review concludes that differentiated media is a strategic instrument for inclusive IPAS learning, recommending future development of adaptive AI-based media and stronger teacher training.